Pengaruh Budaya Organisasi dan Komitmen Karyawan terhadap Organizational Citizenship Behavior (OCB) pada Karyawan di Fakultas Ekonomi Universitas Negeri Padang - Dahlia Dahlia; Tri Kurniawati (Universitas Negeri Padang, 2021)
This study aims to determine the effect of organizational culture and employee commitment on organizational citizenship behavior (OCB) on employees at the Fakultas Ekonomi Universitas Negeri Padang. This research uses three variables, namely Organizational Culture, Employee Commitment, and Organizational Citizenship Behavior (OCB). This type of research is quantitative research with a causal method. The population in this study amounted to 45 employees with sampling using total sampling technique. So that a sample of 45 employees was obtained. Data collection techniques using research questionnaires. The data that has been collected was analyzed using multiple regression analysis, to see the most dominant component of its influence on organizational citizenship behavior (OCB) in employees at the Fakultas Ekonomi Universitas Negeri Padang. The results of this study indicate 1) organizational culture has a positive and significant effect on organizational citizenship behavior (OCB) on employees at the Fakultas Ekonomi Universitas Negeri Padang seen from the sig value. 0.000 < 0.05. 2) employee commitment has a positive and insignificant effect on organizational citizenship behavior (OCB) on employees at the Fakultas Ekonomi Universitas Negeri Padang as seen from 0.498 > 0.05. 3) organizational culture and employee commitment have a positive and significant effect on organizational citizenship behavior (OCB) on employees at the Fakultas Ekonomi Universitas Negeri Padang seen from the sig value. 0.000 < 0.05.Keywords : organizational culture, employee commitment, organizational citizenship behavior (OCB)